Menelusuri Jejak Tafsir Riwayat: Studi Deskriptif atas Tafsir Al-Dur Al-Mansur Karya Al-Suyuti - Didik Harianto; Putroe Balqis (At-Tafasir: Journal of Al-Qur'an Studies and Contextual Tafsir, 2025)
This study examines al-Dur al-Mansur fi al-Tafsir bi al-Ma’tsur by Imam al-Suyuti, a major work in the tradition of tafsir bi al-ma’tsur—Qur’anic exegesis based on transmitted reports from the Prophet, his Companions, and the tabi‘in. Using qualitative library research and content analysis, the study explores al-Suyuti’s method, sources, and the distinctive features of his tafsir within the wider history of Qur’anic interpretation. The findings show that al-Suyuti compiled narrations extensively without adding personal interpretation, relying mainly on hadith, athar, and early scholarly views. While he did not systematically verify the isnad, he often indicated the reliability of certain reports, reflecting his expertise in hadith. His approach was also shaped by the intellectual saqafah of his time, especially the Ash‘ari theological framework and the jurisprudential traditions of the Shafi‘i and Hanafi schools. Al-Dur al-Mansur stands out as an encyclopedic repository preserving earlier tafsir works, including some now lost, distinguishing it from al-Tabari’s Jami‘ al-Bayan, which adopt more selective and analytical approaches. The study suggests further research on the authenticity of its narrations and intertextual comparisons with other tafsir bi al-ma’tsur.